PELATIHAN INSTALASI DAN SETTING RUNNING TEXT UNTUK TAMPILAN INFORMASI DI DESA DUWET KECAMATAN TUMPANG - Donny Radianto; Muhammad Khairuddin; Hari Kurnia Safitri; Subiyantoro; Siswoko (Jurnal Pengabdian Kepada Masyarakat (J-ABDIMAS), 2021)
The development of electronic technology requires the availability of human resources who have adequate skills. This technology can be used not only in the world of education but can also be used as a promotional medium for a superior product. Installation training and running text settings conducted in Duwet Village conducted by the PkM team for youth groups in Duwet Village. It is hoped that with this service activity, Duwet Village residents, especially youth members, are able to install, operate and set running text, so that youth groups there can use running text correctly and can use running text to market their products as much as possible